Strengthening global diversity character through civic education in Pancasila student profile learning - Aziz, Thoriq Abdul; Abdulkarim, Aim; Maulana, Yana (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
The Pancasila Student Profile project at SMA Negeri 3 Cimahi is examined in this study to illustrate how project-based learning and civic education can be combined to increase high school students’ awareness of cultural diversity. The study examines the project’s implementation and its effects on students’ character development using qualitative research techniques like observation, interviews, and document analysis. The research was conducted at SMA Negeri 3 Cimahi in the January 2022/2023 school year with grade X high school students carrying out Project learning. The results demonstrate how the Pancasila Student Profile project offers a strong foundation for promoting student variety, tolerance, and respect for different values crucial for molding their character to embrace global diversity. By allowing students to apply their knowledge and abilities to actual problems, the project also fosters the ability to think critically and solve problems. The study highlights how crucial it is for teachers to get support and training to include civic education in project-based learning. Students can experience character improvement through Project learning by applying the values of the ability to work together and tolerance for other learning outcomes. Teachers may establish a supportive learning environment that supports students’ character development by being given the necessary tools and resources. The study’s findings have significant ramifications for practitioners and educational policymakers who want to strengthen students’ character development and prepare them for the difficulties of living in a diverse and globalized environment.